Pengaruh Brand Personality dan Social Influence Terhadap Repurchase Intention Konsumen Produk Fashion Merek Uniqlo di Kota Cimahi - Rifqi Hafizh; Siti Herawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of brand personality and social influence on the repurchase intention of consumers of Uniqlo fashion products in Cimahi City. The background of this study is based on the decline in revenue of the Uniqlo fashion brand in Indonesia, which indicates a decline in consumer repurchase interest. Brand personality and social influence are considered two important factors in shaping consumer loyalty, but previous studies have shown inconsistent findings. This study employs a quantitative approach using a descriptive method with 90 respondents selected based on predetermined criteria. The research instrument used in this study is a questionnaire that has been tested for validity and reliability, with all items in the instrument deemed valid and reliable. The research data underwent classical assumption tests, with results showing normal distribution, no multicollinearity, and no heteroskedasticity. Data analysis was conducted using multiple linear regression with the assistance of SPSS Version 27 software. The results of the study indicate that, both partially and simultaneously, brand personality and social influence have a significant effect on repurchase intention.